Representation of authors’ worldview in selected poems of Mabala, Summons: poems from Tanzania (A genetic structuralism analysis) - Astelia Mihayo; Ida Bagus Putera Manuaba (EduLite: Journal of English Education, Literature and Culture, 2019)
This paper examines the worldview of Tanzanian poetry in English. It focuses on selected poems of Mabala (1980) entitled Summons: Poems from Tanzania. The study places the poems under Lucien Goldmann’s genetic structuralism approach and argues against the historical context and discourse of Tanzania between 1960s and 1980’s. Specifically, the study analyses the author’s social and historical conditions influenced the production of the Summons poetry and showcases how the author’s worldview in particular poems in general are creatively explored in the social realities. The exploration of worldview in selected poems congruence the social and historical realities and the Socialism ideology [society’s worldview or global structure]. In other words, the exploration of the worldview in the selected poems confirms the homology of the global structure. The poems construct the ideal values of socialist state that seemed relevant in the post-independence Tanzania. They, in one or another provide the historical account for the building of Socialism ideology. They are about and against the ideology which confuse the vision people have of themselves and of their lives and the friction that failed the implementation of Socialism ideology. The study appropriates dialectic method to achieve the coherence of meaning of the text as a whole (poem structure and global structure).